RATES OF FELDSPAR DISSOLUTION AT PH 3-7 WITH 0-8 M M OXALIC ACID - Stillings L.L.; Drever J.I.; Brantley S.L.; Yanting S.; Oxburgh R. (My University, 1996)
Feldspar dissolution rates were measured in flow-through reactors, over a pH range of 3-7, oxalic acid concentration of 0-8 m M, and feldspar compositional range of An0-An76. Dissolution rates in 0 and 1 m M concentrations of oxalic acid increased linearly with increasing mole percent anorthite in the solid. Dissolution was nonstoichiometric in oxalic acid, due to a preferential release of Al at steady state. 1 m M concentrations of oxalic acid increased dissolution rates by a factor of 2-5 at pH 3 and 2-15 at pH 5-6. At pH 5-6 the rate enhancement due to oxalic acid may increase with increasing anorthite content of the feldspar. The ligand-promoted rate, RL, defined as the observed total rate in oxalic acid minus the proton-promoted rate, Rt - RH, was estimated as 10-12.8(aHOx- + aOx2-)0.75, suggesting that both HC2O-4 (bioxalate) and C2O2-4 (oxalate) play a role in the dissolution mechanism.